AtMYB12-Expressing Transgenic Tobacco Increases Resistance to Several Phytopathogens and Aphids - Ding, Xiangyu; Zhang, Haimiao; Li, Ming; Yin, Ziyi; Chu, Zhaohui; Zhao, Xiangyu; Li, Yang; Ding, Xinhua (Frontiers in Agronomy, 2021)
Phytopathogens and pests are two major factors that limit the growth of plants. The expression of a flavonoid regulator gene, AtMYB12(AT2G47460), has been reported to increase the endogenous flavonoid content of tobacco and tomato. Previous research has only focused on the regulation mechanism of v-myb avian myeloblastosis viral oncogene homolog (MYB) transcription factors under single stress conditions. Here, research showed that AtMYB12 was involved in regulating the resistance of tobacco to multiple biological stresses such as phytopathogens and aphid. We reported that transgenic tobacco carrying AtMYB12 was more resistant to Ralstonia solanacearum when the up-regulated expression of several defense-related markers, such as NbPR1a, NbNOA1, and NbrbohB, was activated, suggesting that the priming defense of a plant may contribute to bacterial disease resistance. The improvement of the resistance of AtMYB12-expressing transgenic tobacco is achieved by promoting the production of ROS, H2O2, and NO. AtMYB12-expressing transgenic tobacco also has resistance to fungal pathogens, such as Colletotrichum nicotianae Averna and Alternaria alternate. The enrichment of flavonols components, such as rutin, which directly inhibit the growth of C. nicotianae and A. alternate, may also contribute to the defense mediated by AtMYB12 over-expression. At the same time, the results also confirm that AtMYB12-expressing transgenic tobacco enhanced plant resistance to aphid-infested (Aphidoidea) pests. These results suggest that the AtMYB12 gene is a good candidate for pest and disease control, with limited resistance costs and enrichment in flavonols, and that AtMYB12 has a potential in the breeding of disease-resistant tobacco crops.